2018
DOI: 10.7126/cumudj.414992
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Carabelli’s trait in a group of Turkish patients

Abstract: Dental morphological characteristics are useful for providing information in phylogenic and genetic studies and also for understanding variations within and among species. Carabelli cusp is expressed in several degrees and in different frequencies among humans; thus, it is helpful in comparing and characterizing populations. The objective of this retrospective study was to evaluate Carabelli's trait (CT) in a group of Turkish patients. Materials and Methods: In this study, 213 patients between age of 14-65 (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Also, if the trait is present on the second and third molars it is likely that it will be found on the first molars as well (6,12,17,18,23,29,30,32). The total frequencies of the trait range from 0% to 25% for second molars (6,12,17,18,23,26,29,30,32,36), and from 0% to 17% for third molars (18,29,32) among various populations. The distal decreases in the frequency of the trait from the maxillary second deciduous molars to the third permanent molars have been attributed to environmental factors or epigenetic influences operating during their development, with latedeveloping teeth in a morphological field having greater environmental variability (16,29,37).…”
Section: Discussionmentioning
confidence: 99%
“…Also, if the trait is present on the second and third molars it is likely that it will be found on the first molars as well (6,12,17,18,23,29,30,32). The total frequencies of the trait range from 0% to 25% for second molars (6,12,17,18,23,26,29,30,32,36), and from 0% to 17% for third molars (18,29,32) among various populations. The distal decreases in the frequency of the trait from the maxillary second deciduous molars to the third permanent molars have been attributed to environmental factors or epigenetic influences operating during their development, with latedeveloping teeth in a morphological field having greater environmental variability (16,29,37).…”
Section: Discussionmentioning
confidence: 99%
“…Presence of such tubercle on the other molar tooth is less frequent. 2 These are usually bilateral and are more frequent in men compared to women though the difference is insiginificant. So gender does not have any significant association.…”
Section: Introductionmentioning
confidence: 99%
“…So gender does not have any significant association. 2,3 Studies have shown that its frequency varies among different populations. It may provide a clue for racial differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation